2015
DOI: 10.1371/journal.pone.0140980
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Symptoms and Risk of Burnout in Child Care Workers — A Cross-Sectional Study

Abstract: ObjectivesGerman child care workers' job satisfaction is influenced by the consequences of unfavourable underlying conditions. Child care workers tend to suffer from psychosocial stress, as they feel that their work is undervalued. The objective of the present study is to investigate how the psychosocial factors of the effort-reward imbalance (ERI) model influence musculoskeletal symptoms (MS) and the risk of burnout. To our knowledge this is the first study investigating the association between the factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 49 publications
(48 reference statements)
1
33
2
Order By: Relevance
“…Objective measurements have found that the peak sound pressure in these institutions is greater than 85 dB(A) [1–5], which confirms the employees’ subjective impression [1, 6, 7]. This noise is mostly caused by the children’s voices and their playing [4].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Objective measurements have found that the peak sound pressure in these institutions is greater than 85 dB(A) [1–5], which confirms the employees’ subjective impression [1, 6, 7]. This noise is mostly caused by the children’s voices and their playing [4].…”
Section: Introductionmentioning
confidence: 72%
“…The structural causes of the noise exposure and possibly also burnout risk in this group are presumably inadequate numbers of employees, excessively large groups and, especially, too few trained child care workers [7]. These issues have long been discussed by politicians with expertise in employment and could only be modified at another level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Koch et al [231] investigated how psychosocial factors influence MSD, in addition to the risk of burnout among infant caretakers within the German labour system. Siivola et al [221] studied a sample of teenage students to ascertain the way in which neck and shoulder pain is related to cervical alterations found by nuclear magnetic resonance.…”
Section: Authors Location Observationsmentioning
confidence: 99%